(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Sustainable agriculture practices, characterized by their holistic approach to balancing environmental, economic, and social dimensions, represent a transformative paradigm in the pursuit of global food security. This abstract encapsulates a multidimensional analysis of key parameters essential to sustainable agriculture, presented in a structured table format. The parameters, including Agroecology, Crop Diversity, Water Management, Soil Health, Integrated Pest Management, Social Equity, Technology and Innovation, Policy and Advocacy, Educational Initiatives, Global Cooperation, Economic Viability, Indigenous Wisdom, Governance for Sustainability, and Consumer Awareness, are systematically explored. The importance of each parameter is highlighted, emphasizing their positive impacts on soil fertility, resilience, efficient resource use, and ethical practices. Challenges associated with transition costs, resistance to change, and limited accessibility are identified. Opportunities, such as increased efficiency, biodiversity preservation, and poverty reduction, are presented as potential outcomes of addressing these challenges. This parameterized analysis serves as a comprehensive tool for stakeholders, offering insights into the interconnected nature of sustainable agriculture practices. It provides a foundation for informed decision-making, fostering collaboration among farmers, policymakers, researchers, and consumers. The abstract concludes with the recognition that sustainable agriculture is an evolving journey, requiring continuous adaptation, innovation, and global cooperation to nurture a resilient, inclusive, and sustainable future for agriculture and food systems.